The Accusative‐Subject Generalization. (27th July 2017) - Wood, Jim
Abstract: This article discusses the morphosyntax of accusative‐subject constructions in Icelandic, from the point of view of the "dependent case" analysis of accusative. The primary focus is on deriving the Accusative‐Subject Generalization (ASG), the generalization that accusative subjects are never related thematically to a morphologically intransitive verb. After it is demonstrated that the ASG holds, it is proposed that the ASG follows from the claim that there is no such thing as inherently case‐marked accusatives in Icelandic. The accusative‐subject constructions under scrutiny in fact involve a silent external argument that distributes like a clitic syntactically and is interpreted like a weather pronoun semantically. The account is explanatory insofar as it involves one stipulation—the presence of a silent clitic—from which the ASG and numerous other syntactic, semantic, and morphological properties of accusative‐subject constructions follow. The explanatory value of the account hinges on a grammatical architecture in which morphological idiosyncrasy and semantic idiosyncrasy are computed in distinct components of the grammar, and case marking—even structural case marking—is divorced from DP licensing.